Fatigue resonant tests on drill collar rotary shouldered connections and critical thread root identification. (July 2018) - Santus, C.; Bertini, L.; Burchianti, A.; Inoue, T.; Sakurai, N.
Abstract: A fatigue test series on a drill collar rotary shouldered connection, thread type 5-1/2 FH MOD, was performed with a dedicated alternating bending resonant test rig. Compared to a quasi-static testing approach, the dynamic loading allowed high testing frequency and a relatively light supporting structure. Crack initiation was identified as the onset of a discrepancy between two strain gauge signals which were monitored throughout the test. A through-wall crack condition was assumed as the effective fatigue failure. The stress distribution in the connection was then analysed with a finite element plane harmonic axisymmetric model, taking into account both the initial make-up torque and the alternating bending load during the test. In these simulations, the most critical stress between the pin or box, in terms of fatigue, mainly depended on the preload. The modelled contact behaviour of the incomplete threads of the box played a significant role in predicting the position of the crack initiation thread root, which was then compared with the test results. Highlights: Resonant test rig for fatigue full scale testing large diameter tubular connections. Drill collar threaded connection 5-1/2 FH MOD test results. Fatigue crack initiation evidence at the box LET before the incomplete threads. FE analysis to predict the correct thread root and role of the incomplete threads. Make-Up torque effect on the predicted critical root between pin FET and box LET.